Estimated Number of Palm Oil Production Using Artificial Neural Networks at the North Sumatra Province Plantation Service - Majidah, Nur; Dur, Sajaratud; Aprilia, Rima (Justek : Jurnal Sains dan Teknologi, 2023)
Abstract:  Artificial Neural Network is an information processing system that is designed to imitate the workings of the human brain in solving problems by carrying out a learning process. In 2019 the total production of palm oil at People's Plantations was 7,006,986.36 tons, PTPN 5,541,934.78 tons, PBS 12,574,520.68 tons. In 2020 the total production of palm oil in People's Plantations increased to 7,199,750.00 tons, while PTPN decreased to 5,500,327.63 tons, PBS decreased to 11,361,158.60 tons. In 2021 the total production of palm oil in the three agencies will increase, namely in the People's Plantations 7,451,890.91 tons, PTPN 5,809,316.15 tons, PBS 11,631,135.30 tons. Therefore a system is needed that is able to estimate the amount of palm oil production in the future, namely in 2022. The Artificial Neural Network Backpropagataion method is used to estimate the annual data on the amount of palm oil production in order to find out the results of the amount of palm oil production. There is an estimation of the total production of palm oil which is 24.432.878,09 tons of production consisting of smallholders' plantations is 7.134.629,47 tons, PTPN is 5.588.976,44 tons, PBS is 11.709.272,18 tons. It is highly probable that the estimated amount of palm oil production in 2022 will increase. Abstrak: Artificial Neural Network adalah suatu sistem pemrosesan informasi yang didesain dengan meniru cara kerja otak manusia dalam menyelesaikan masalah dengan melakukan proses belajar. Pada tahun 2019 jumlah produksi kelapa sawit pada Perkebunan Rakyat 7.006.986,36 ton, PTPN 5.541.934,78 ton, PBS 12.574.520,68 ton. Pada tahun 2020 jumlah produksi kelapa sawit pada Perkebunan Rakyat meningkat mencapai 7.199.750,00 ton,  sedangkan pada PTPN menurun mencapai 5.500.327,63 ton, PBS menurun mencapai 11.361.158,60 ton. Pada tahun 2021 jumlah produksi kelapa sawit pada ketiga instansi mengalami peningkatan yaitu pada Perkebunan Rakyat 7.451.890,91 ton, PTPN 5.809.316,15 ton, PBS 11.631.135,30 ton. Oleh karena itu dibutuhkan sistem yang mampu mengestimasikan jumlah produksi kelapa sawit di masa yang akan datang yaitu pada tahun 2022. Metode Artificial Neural Network Backpropagataion digunakan untuk melakukan estimasi terhadap data tahunan jumlah produksi kelapa sawit agar dapat mengetahui hasil jumlah produksi kelapa sawit. Terdapat hasil estimasi jumlah produksi kelapa sawit adalah 24.432.878,09 ton produksi yang terdiri dari Perkebunan Rakyat adalah 7.134.629,47 ton, PTPN adalah 5.588.976,44 ton, PBS adalah 11.709.272,18 ton. Besar kemungkinan estimasi jumlah produksi kelapa sawit pada tahun 2022 akan turun.